Ekspektasi Sosial Pemuda Sasak dalam Nasyid Ya Fata Sasak Karya Hamzanwadi - Akhyar Rosidi (Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Ilmu Pendidikan, Universitas Timor, 2018)
This study aims to describe the youth’s social expectations of the nasyid text Ya Fata Sasak by T.G.K.H. Muhammad Zainuddin Abdul Majid. The research method used is semiotic that is qualitative interpretive with content analysis techniques that focus to the research on the latent content of nasyid text Ya Fat Sasak as data research on the latent content of the nasyid Ya Fata Sasak research. This technique is carried out by copying the nasyid Ya Fata Sasak manuscript to Indonesian, reading, writing, and coding into five codes of Rolands Barthes such as hermeneutic code, action code, symbolic code, semantics code, and referential code. So the social expectations of the Sasak youth are defined. The result of this research shows that Sasak youth have equal opportunities with other young people in Indonesia to expect both individually and collectively. Every social expectation carried out by Sasak youth is certainly related to the interest of the people, nation and the state which is realized through the strengthening of critical and independent discourses to maintain their idealism, such as building self-confidence (character building) and carrying out social and religious values as brotherhood and unity, managing natural resources that can be utilized optimally, participating in various competitions of contestations, and instilling a spirit of nationalism as the one of foundations for maintaining and advancing the Indonesian people.